2021
DOI: 10.51791/njap.v44i3.751
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of beef sausage containing varying levels of ginger (Zingiber officinale) powder

Abstract: Quality of beef sausage with varying levels of ginger powder as seasoning was investigated. Batch 1 was the Control (0% Ginger powder), Batch 2 had 25% of the seasoning as Ginger powder , Batch 3 had 50% of the seasoning as Ginger powder of total seasoning), Batch 4 had 75% of the seasoning as Ginger powder and Batch 5 had 100% of the seasoning as Ginger. Parameters measured were all subjected to one-way analysis of variance. Results obtained were significantly (P<0.05) different. For cooking and refrigerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The incorporation of llers into meat products such as sausages has some advantages such as increasing the product yield and quality, enhancing the formulation properties, improving the health and nutritional benets, and reducing cost. 56,57 Positive results have been reported in the incorporation of different llers such as tapioca starch and our from wheat, cassava, rice, coconut, and high-quality cassava 55,[58][59][60] in sausages. A comparison of the optimized sample with the control revealed that the control sample had higher mean values for moisture, fat, and protein contents.…”
Section: Comparison Of the Characteristics Of Optimized Hot-air And D...mentioning
confidence: 99%
“…The incorporation of llers into meat products such as sausages has some advantages such as increasing the product yield and quality, enhancing the formulation properties, improving the health and nutritional benets, and reducing cost. 56,57 Positive results have been reported in the incorporation of different llers such as tapioca starch and our from wheat, cassava, rice, coconut, and high-quality cassava 55,[58][59][60] in sausages. A comparison of the optimized sample with the control revealed that the control sample had higher mean values for moisture, fat, and protein contents.…”
Section: Comparison Of the Characteristics Of Optimized Hot-air And D...mentioning
confidence: 99%